Estimating the Some Biochemical Variables in Patients with Diabetic Kidney - Hamed Al-Qaisi, Ahmed Nayef; Al_Samarrai, Nuha Ali Hadi (American Journal of Bioscience and Clinical Integrity, 2025)
The research sought to evaluate the efficacy of the arginase enzyme in patients with type 1 diabetes mellitus in Samarra city. Ninety samples were obtained from male and female patients aged 30 to 70 years at Samarra General Hospital, covering the period from January 10, 2024, to December 30, 2024. The investigation included the assessment of urea, creatinine, uric acid, total protein, albumin, glucose, iron, glutathione, glutathione peroxidase, and superoxide dismutase (SOD). The results showed an increase in the activity of arginase enzyme, urea, creatinine, iron, total protein, glucose and antioxidants in the group of patients compared to healthy people at the probability level p<0.0001. Regarding gender, there was a notable elevation in uric acid and SOD levels in the female cohort, with p<0.005 in comparison to men. Creatinine and glucose levels were elevated in men relative to healthy individuals. The other factors did not exhibit significant changes based on sex.